Analysis of Students' Errors in Solving Class III C Mathematics Story Questions at SDNU - Ismi Ma'lufah, Dina Zulva; Muh Ngali Zainal Makmun (Journal of Research in Islamic Education, 2025)
This study aims to analyze various forms of errors made by grade III C students at SDNU in an effort to solve mathematics problems in the form of narratives or story problems, this study applies a qualitative descriptive approach involving 27 students as participants. Data were collected through written tests and interviews. to identify the types of errors that appear at each stage of problem solving, namely understanding the problem,planning the solution, implementing the solution, and checking the results. The results of the study revealed that the most common errors occurred at the stages of understanding the problem, planning the solution, implementing the solution, and re-checking. Factors causing errors include a lack of understanding of basic concepts, low reading ability, and the teaching approach used is not optimal. Thus, this study recommends improvements in learning strategies, including regular practice of story problems and the use of varied methods, to help students improve their skills in solving mathematics story problems.